Mental health and body image among SGM youth engaged with a digital eating disorder intervention - Kasson, Erin; Szlyk, Hannah S; Li, Xiao; Sirko, Georgi; Rehg, Isabel; Vázquez, Melissa M; Wilfley, Denise E; Barr Taylor, C; Fitzsimmons-Craft, Ellen E (Journal of LGBT youth, 2025)
Sexual and gender minority (SGM) teens may experience body image concerns and eating disorders (EDs) at higher rates than their non-SGM peers. The current investigation examined differences in baseline survey responses by SGM and non-SGM youth who participated in a pilot randomized controlled trial of a digital intervention for EDs. Eligible teens (N=147) aged 14-17 years old who screened positive or at high risk for an ED completed a baseline survey to assess current ED symptoms, mental health comorbidities, and ED treatment history. The majority of participants (mean age 16.021 years) screened positive for symptoms of a clinical/subclinical ED (n=98, 66.7%), 123 endorsed severe anxiety (83.7%), and 81 endorsed severe depression (55.1%). A total of 72.1% (n=106) identified as SGM and were more likely to report severe symptoms of depression ( = 0.01), any symptoms of anxiety ( = 0.03), social anxiety disorder ( = 0.02), and lifetime suicide attempts ( <.001), compared with non-SGM peers. Qualitative feedback on the intersection of SGM identities and body image concerns were also reported among SGM teens. Future eating disorder interventions provided to SGM youth should include content on comorbidities like depression and anxiety, which may be barriers to ED recovery among SGM teens.